Integrating Integrity in Teachers’ Pedagogy - Dumopoy, Edwin (Journal of Interdisciplinary Perspectives, 2025)
Integrity, recognized as a cornerstone of ethical behavior in education, is essential in fostering high teaching standards and student development. This study explores the integration of integrity into pedagogical practices among 202 secondary teachers in the District of Pontevedra, focusing on elements such as academic honesty, equality, ethical decision-making, preparation, delivery, and intention in teaching. Understanding the relationship between integrity and pedagogy is critical in ensuring ethical instruction, maintaining trust in the educational system, and reinforcing professionalism in teaching. The study examines the level of integrity and the degree of pedagogy among teachers, identifying variations based on age, sex, position, educational attainment, and length of service. Addressing overlooked aspects, such as student perspectives and institutional integration of integrity, this research fills a gap in understanding how educational institutions in the Philippines, particularly in Capiz, embed integrity within academic practices. Employing a quantitative descriptive-correlational research design, data were gathered through a researcher-made questionnaire validated by experts and pilot-tested with 30 non-participant teachers to ensure reliability. The analysis, conducted using IBM SPSS Statistics version 26, applied statistical methods such as frequency, mean, t-test, f-test, and Pearson’s correlation. Results revealed a very high level of integrity and pedagogy among teachers, with significant differences in integrity based on position and in pedagogy based on sex. The study underscores the strong relationship between integrity and pedagogy, highlighting specific areas where integrity enhances teaching effectiveness. It urges educational institutions and policymakers to support initiatives that cultivate integrity in teaching, reinforcing its role in upholding ethical standards and improving instructional quality.